Tracking vessels in tissue culture laboratory using RFID system and LDR sensor / Nurul Syahrini Mat Koris - Mat Koris, Nurul Syahrini
Tissue culture laboratory at Malaysian Palm Oil Board (MPOB) is a place that involved in producing superior planting material through tissues culture or cloning process. In the tissue culture laboratory, a lot of vessels for cloning process arc located in several racks with different growth rooms. All the data specification of vessels such as date, the person who doing the cloning process, and number of racks arc recorded manually on log book for the future references. Besides that, the data of tracking the vessel such as time and who take out the vessels also done manually. This project proposed a Radio Frequency Identification (RFID) system with Light Dependent Resistors (LDR) sensor to replace the current method of data tracking vessels. This project consists of two main parts which are hardware and software. In hardware part, the main component is RFID card, PIC 16F877A, and Light Dependent Resistors sensor to detect the vessels. Meanwhile, for the software part, visual basic software is used to display the information or data. Tested has been performed and the result show the improvement of the tracking vessel system in the tissue culture laboratory.